AB0543 Anxiety and depression in chinese patients with primary sjÖgren's syndrome. (15th June 2017) - Cui, Y; Li, L; Zhao, Q; Chen, S; Li, L; Gu, Z
Abstract : Background: Primary Sjögren's syndrome (pSS) is a multisystem autoimmune disorder characterised by lymphocytic infiltration and exocrine failure of salivary and lacrimal glands, resulting in the classical symptoms of the disease including xerostomia (dry mouth) and keratoconjuctivitis sicca (dry eyes). pSS has the potential to impair both psychological state and the health-related quality of life (HR-QOL). A common mental health problem among adults with pSS is anxiety and depression. In addition, depression is more common in pSS than in the general population and has been associated with enhanced fatigue, reduced health-related quality of life, increased levels of physical disability and increased health care costs. Besides, depressed pSS patients have poorer long-term outcomes, including more complications. Anxiety was more common than depression in pSS. The most affected domains were vitality in the SF-36 and general/physical fatigue in the MFI. Extraglandular systemic involvement was not a major determinant of QoL alteration in patients with pSS. Objectives: Prevalence of anxiety and depression are high in women with Primary Sjögren's syndrome (pSS). Our aim was to compare anxiety and depression in pSS patients and healthy controls and evaluate its relationship with the disease activity, sleep and quality of life; as well as to analyze potential determinants of anxiety and depression. Methods: Sixty-seven patients fulfilling the American-European Consensus Group criteria for pSS (mean age 52.76 years (s.d. 13.16)) and 42 age-matched healthy controls were included. Participants completed self-administered questionnaires, namely Hospital Anxiety and Depression Scale (HADS), Short Form 36 (SF-36) scores and the Pittsburgh Sleep Quality Index (PSQI). In addition, the European League Against Rheumatism Sjögren's Syndrome Disease Activity Index (ESSDAI); Patient Reported Index (ESSPRI) and systemic inflammation (erythrocyte sedimentation rate (ESR), C-reactive protein (CRP) level) were recorded in patients. Independent samples t-tests, χ2 analyses and logistic regression modeling were used to analyze the data. Results: pSS patients experienced greater anxiety and depression than controls (HADS-A scores: mean± SD 6.5±3.4 for pSS versus 3.8±3.4 for controls; P =0.002. HADS-D scores: mean± SD 6.7±4.1 for pSS versus 4.2±3.5 for controls; P =0.012). And there were significant correlations among fatigue, pain, disease activity, dryness, sleep, quality of life and anxiety/depression. Meanwhile, logistic regression analysis revealed that poor quality of life and ESSPRI were significantly associated with anxiety/depression in pSS patients. Conclusions: The study suggests that optimal care of pSS patients may include the detection and management of anxiety and depression. Early recognition and appropriate intervention is therefore essential to reduce the negative impact of anxiety and depression on the patient's quality of life and outcome of their disease. Acknowledgements: This research was supported by grants from the National Natural Science Foundation of China (81471603, 81172841); "Top Six Types of Talents" Financial Assistance of Jiangsu Province (Grant no. 10.WSN016). Disclosure of Interest: None declared